In vitro extinction learning in Hermissenda: involvement of conditioned inhibition molecules - Cavallo, Joel S.; Hamilton, Brittany N.; Farley, Joseph (Frontiers in Behavioral Neuroscience, 2014)
Extinction of a conditioned association is typically viewed as the establishment of new learning rather than the erasure of the original memory. However, recent research in the nudibranch, Hermissenda crassicornis (H.c.) demonstrated that extinction training (using repeated light-alone presentations) given 15 min, but not 23 hr, after memory acquisition reversed both the cellular correlates of learning (enhanced Type B cell excitability) and the behavioral changes (reduced phototaxis) produced by associative conditioning (pairings of light, CS, and rotation, US). Here, we investigated the putative molecular signaling pathways that underlie this extinction in H.c. by using a novel in vitro protocol combined with pharmacological manipulations. After intact H.c. received either light-rotation pairings (Paired), or no stimulation (Untrained), B cells from isolated CNSs were recorded from during exposure to extinction training consisting of two series of 15 consecutive light-steps (LSs). When in vitro extinction was administered shortly (2 hr, but not 24 hr) after paired training, B cells from Paired animals showed progressive and robust declines in spike frequency by the 30th LS, while Untrained cells did not. We found that several molecules implicated in H.c. conditioned inhibitory (CI) learning, protein phosphatase 1 (PP1) and arachidonic acid (AA)/12-lipoxygenase (12-LOX) metabolites, also contributed to the spike frequency decreases produced by in vitro extinction. Protein phosphatase 2B (PP2B) also appeared to play a role. Calyculin A (PP1 inhibitor), cyclosporin A (PP2B inhibitor), and baicalein (a 12-LOX inhibitor) all blocked the spike frequency declines in Paired B cells produced by 30 LSs. Conversely, injection of catalytically-active PP1 (caPP1) or PP2B (caPP2B) into Untrained B cells partially mimicked the spike frequency declines observed in Paired cells, as did bath-applied AA, and occluded additional LS-produced reductions in spiking in Paired cells.